ANALISIS MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP KEMAMPUAN BERFIKIR KRITIS SISWA KELAS IV C PADA PEMBELAJARAN TEMATIK DI SD ISLAM SURYA BUANA MALANG - Ameylia Fatmawathus Sholichah; Muhammad Hanief; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
The ability to think critically is a basic asset that must be possessed by students. Critical thinking is an intellectual process for searching and finding one's knowledge (self-regulated). Unfortunately, the level of critical thinking possessed by students in Indonesia is still relatively low. The teacher needs to think of ways to develop these skills. One of them is by using a learning model. Therefore, this study will examine the application of the CTL model to see the development of students' critical thinking skills. This research uses a qualitative approach to the type of case study. Data were collected by conducting interviews, observations, and documentation of fourth-grade teachers at SDI Surya Buana Malang as subjects in this study. The results showed that teachers need to prepare learning tools before starting teaching and learning activities. The learning process conducted by the teacher with the CTL learning model has a positive impact on improving students' critical thinking skills. This is indicated by the active role of students who always ask questions about the problems presented in learning.Key words : Contextual Teaching And Learning, Critical Thinking, Thematic Education